Mass mortality of fingerlings of Labeo rohita (Hamilton) in a nursery pond - Sugumar, G; Karunasagar, Indrani; Karunasagar, Iddya (Indian Journal of Fisheries, 2011)
The cause of large scale mortality in fingerlings of Labeo rohita (Hamilton) stocked in a nursery pond was investigated. Examination of gills of healthy looking fingerlings revealed heavy infestations of Dactylogyrus. Bacteriological studies showed presence of Aeromonas hydrophila, A.sobria, Vibrio Spp. and enterobacteriaceae in the internal organs of infected fingerlings. Dip treatment of fingerlings in formalin solution (50 ppm) controlled the mortality. Mortality ceased after one week of treatment . Examination of healthy fish at this stage showed absence of Dactylogyrus on the gills and bacteria in the internal organs. Presence of different types of bacteria in Dactylogyrus infected fish suggests that bacteria might have gained entry into the internal organs through damaged gills